Resources for Children with Visual Impairments in Integrated ECD Centers - Shinali, Maryconsolata C.; Githui, Millicent W.; Koech, Peter K. (7MERC Global’s International Journal of Social Science & Management, 2013)
This paper discuses learning resources for children with visual impairments in integrated ECDE Centres. Early childhood care and education has been prioritised as a foundation for later learning and development. It is a global endeavour as evidenced by the global guidelines for early childhood education and care in the 21st century. Children with special needs in education required appropriate adoptions to curricula, teaching methods, educational resources, medium of communication and the learning environment in order to cater for individual differences in learning. This paper intends to critically analyse the adequacy of the learning resource for children with visual impairment at the pre-school level in regular schools. The policy must address the issues of vulnerable and marginalised children, especially children with special needs and provide affirmative action for them. The policy further goes on to state that there should be non-discrimination of children and families on the basis of gender, race, colour, religion, economic status, disability and health status. It is in this view that the paper intends to critically analyse the provision of learning resource for children with visual impairment
Keywords: Visual impairment; Early childhood education; Resources; Integration.